The Politics of Affective Societies : An Interdisciplinary Essay /: An Interdisciplinary Essay. ([2019]) - Bens, Jonas; Diefenbach, Aletta; John, Thomas; Lehmann, Hauke; Lüthjohann, Matthias; Oberkrome, Friederike; Roth, Hans; Scheidecker, Gabriel; Thonhauser, Gerhard; Ural, Nur Yasemin; Wahba, Dina; Walter-Jochum, Robert; et al.
No abstract available